Abnormal salience signaling in schizophrenia: the role of integrative beta oscillations - Liddle, Elizabeth B.; Price, Darren; Palaniyappan, Lena; Brookes, Matthew J.; Robson, Siân E.; Hall, Emma L.; Morris, Peter G.; Liddle, Peter F. (Wiley, 2016)
Aberrant salience attribution and cerebral dysconnectivity both have strong evidential support as core dysfunctions in schizophrenia. Aberrant salience arising from an excess of dopamine activity has been implicated in delusions and hallucinations, exaggerating the significance of everyday occurrences and thus leading to perceptual distortions and delusional causal inferences. Meanwhile, abnormalities in key nodes of a salience brain network have been implicated in other characteristic symptoms, including the disorganization and impoverishment of mental activity. A substantial body of literature reports disruption to brain network connectivity in schizophrenia. Electrical oscillations likely play a key role in the coordination of brain activity at spatially remote sites, and recent, evidence implicates beta band oscillations in long-range integrative processes. We used magnetoencephalography (MEG) and a task designed to disambiguate responses to relevant from irrelevant stimuli to investigated beta oscillations in nodes of a network implicated in salience detection and previously shown to be structurally and functionally abnormal in schizophrenia. Healthy participants, as expected, produced an enhanced beta synchronisation to behaviourally relevant, as compared to irrelevant, stimuli, while patients with schizophrenia showed the reverse pattern: a greater beta synchronisation in response to irrelevant than to relevant stimuli. These findings not only support both the aberrant salience and disconnectivity hypotheses, but indicate a common mechanism that allows us to integrate them into a single framework for understanding schizophrenia in terms of disrupted recruitment of contextually appropriate brain networks.